Spiritual healing from Iranian cancer patients' viewpoints: A hybrid concept analysis - Forough Rafii; Fereshteh Javaheri Tehrani; Maryam Saeedi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Spiritual healing is a complementary and alternative treatment with different meanings in different cultures and religions. However, the concept has not been defined from the cancer patients' points of view. The present study was done with the aim of concept analyses of spiritual healing from Iranian cancer patients' viewpoints. METHODOLOGY: The study was done using a hybrid method at three phases including of theoretical study, field study, and final analysis. In the theoretical study phase and using the keyword "spiritual healing," pertinent articles were searched in main databases. In the field study phase, ten cancer patients were interviewed, and in the final phase, the two other phases were analyzed. After determining features, antecedents, and consequences, a conclusive definition of spiritual healing from Iranian cancer patients' viewpoints was proposed. FINDINGS: Spiritual healing from Iranian cancer patients' viewpoints was featured with four themes, including connection with paranormal forces; effective, noninvasive, inexpensive, and efficient therapeutic method; a way to achieve piece, adaptation, and health and influenced by cultural and religious beliefs. Spiritual healing is a complementary and alternative treatment that helps careseekers to achieve health through paranormal forces and energies. As the findings showed and according to the participants' viewpoints, the source of such forces and energies was divine force and the healers were mediums to transfer the energy. CONCLUSION: The findings supported that religion and faith were the key elements of spiritual healing in the Iranian Islamic context.